Study on current practice of solid waste management system in Gambang residential area Kuantan, Pahang - Nor Zariefa, Zahari (2016)
Nowadays, the Municipal Solid Waste is the one of the environmental problem that needed to give attention in Malaysia. The total amount of waste generated continues to increase in response to rapid increasing in population, urbanization and industrialization process. This research aims to identify the different type of solid waste from residential area in Gambang, Kuantan Pahang and to reduce the total amount of waste generated for sustainable waste management. Sources of the data and information are gathered by the researcher from the literature review of previous researches, published articles, and academic writings and provided suggestions to improve MSW management system in Malaysia. The standard procedure was followed to conduct the research. This study found that there were 6 types of residential waste such as food waste, paper, glass, plastic, tin or aluminium and others. The percentage of the solid waste was about 53 to 63 of food waste, 6 to 8 of papers, 8 to 11 of plastics waste, 4 to 7 of glass, 6 to 8 aluminium and others waste was about 13. Hence these studies suggest that effort to improve awareness of the population involved and practicing to reduce the waste produce, reuse and the use of recycling bins and sorting of solid waste in order to preserve the environment.